M1 macrophage inhibits ferroptosis in Pseudomonas aeruginosa-induced kidney epithelial cell injury through the iNOS/ NO pathway without thiol - Lu, Peixiang; Bai, Xiaojie; Guo, Linfa; Tuoheti, Kuerban; Zhan, Shanzhi; Liu, Tongzu (Frontiers in Cell and Developmental Biology, 2025)
InstructionPseudomonas aeruginosa (PA) is one of the common pathogens of urinary tract infection. It can lead to urosepsis and renal damage. However, the mechanism by which P. aeruginosa affects epithelial cells is not clear.MethodsHK2 cells were treated with extracted PA supernatant (PA.sup). Different pathway inhibitors were added, and similar treatments were applied to HK2 cells co-cultured with macrophages. Cell viability, ferroptosis-related markers, and lipid peroxidation levels were measured.ResultsWe found that PA induced lipid peroxidation using its specially secreted 15-lipoxygenase (ploxA), thereby triggering ferroptosis in epithelial cells. And PA can also damage the GPx4/GSH defense system of epithelial cells. This effect is not through the proteasome pathway but through activating lysosomal chaperone-mediated autophagy (CMA) to reduce the host's GPx4 expression. Then macrophages inhibited lipid peroxidation and protected cells lacking GPx4/GSH through iNOS/NO•.DiscussionWe demonstrated that NO• produced by macrophages can remotely prevent PA-induced ferroptosis of renal epithelial cells. When iNOS, which is responsible for NO• production, is pharmacologically inhibited, the antiferroptotic effect of NO• is reduced. In conclusion, our study reveals an intercellular mechanism for inhibiting ferroptosis, which may provide a new strategy for the host to combat P. aeruginosa -induced ferroptosis.